2011
DOI: 10.4315/0362-028x.jfp-11-213
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Automated BAX PCR and Standard Culture Methods for Detection of Listeria monocytogenes in Blue Crabmeat (Callinectus sapidus) and Blue Crab Processing Plants

Abstract: This study compared the automated BAX PCR with the standard culture method (SCM) to detect Listeria monocytogenes in blue crab processing plants. Raw crabs, crabmeat, and environmental sponge samples were collected monthly from seven processing plants during the plant operating season, May through November 2006. For detection of L. monocytogenes in raw crabs and crabmeat, enrichment was performed in Listeria enrichment broth, whereas for environmental samples, demi-Fraser broth was used, and then plating on bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In 2000, imitation crabmeat was identified as a source of a small listeriosis outbreak in which L. monocytogenes serotype 1/2b strains were isolated from healthy individuals; these cases were traced to consumption of imitation crabmeat, which contained 2.1 × 10 9 CFU/g in a household refrigerator (Farber and others ). Pagadala and others () observed L. monocytogenes in 6.1% of RTE crabmeat samples collected monthly from 7 processing plants during the plant operating season in the U.S.A. The same group performed a more comprehensive study using 1248 samples (environmental and product) and observed L. monocytogenes in 0.2% of cooked crabmeat samples and 2.1% of processing environment samples.…”
Section: Prevalence Of L Monocytogenes In Water Aquatic Food Producmentioning
confidence: 97%
“…In 2000, imitation crabmeat was identified as a source of a small listeriosis outbreak in which L. monocytogenes serotype 1/2b strains were isolated from healthy individuals; these cases were traced to consumption of imitation crabmeat, which contained 2.1 × 10 9 CFU/g in a household refrigerator (Farber and others ). Pagadala and others () observed L. monocytogenes in 6.1% of RTE crabmeat samples collected monthly from 7 processing plants during the plant operating season in the U.S.A. The same group performed a more comprehensive study using 1248 samples (environmental and product) and observed L. monocytogenes in 0.2% of cooked crabmeat samples and 2.1% of processing environment samples.…”
Section: Prevalence Of L Monocytogenes In Water Aquatic Food Producmentioning
confidence: 97%
“…The overarching goal of these studies was to develop and test detection methods that were more sensitive, more rapid and/or more cost effective, focusing on optimizing the enrichment steps and differential culture media or developing automated molecular methods. Eight studies validated detection techniques involving PCR (both commercial and lab‐scale) compared to traditional culturing methods (either ISO or FDA approved methods) (Bolocan et al., ; D'Amico & Donnelly, ; Dalmasso et al., ; Hoffman & Wiedmann, ; Kovacevic et al., ; Medrala, Dabrowski, & Szymanska, ; Norton, Wiedmann, Boor, & McCamey, ; Pagadala, Parveen, Schwarz, Rippen, & Luchansky, ). Three studies compared commercial detection techniques (Kabuki, Boor, Wiedmann, & Kuaye, ; Schirmer, Langsrud, Moretro, Hagtvedt, & Heir, ; Vongkamjan, Fuangpaiboon, Jirachotrapee, & Turner, ).…”
Section: Resultsmentioning
confidence: 99%